Molecular phylogeny of Hipparchia Fabricius, 1807 (Lepidoptera: Nymphalidae: Satyrinae) with description of an overlooked species from the Zagros mountains, Iran - Naderi, Alireza; Hagen, Wolfgang Ten; Nazari, Vazrick (Zootaxa, 2025)
Using sequence data from four nuclear genes alongside DNA barcodes, we reconstructed the evolutionary history of genus Hipparchia Fabricius, 1807. Our phylogeny supported the previously proposed subgeneric classification for the genus and revealed an overlooked taxon close to H. fatua (Freyer, 1845) from the Zagros mountain range in Western Iran, here described as a new species, Hipparchia lunulata sp. nov. We also confirm that the range of H. fatua sichaea (Lederer, 1857), originally described from Beirut, extends to the westernmost part of the Zagros mountains in Iran.